Innovative Applications of Intangible Cultural Heritage: The Inheritance of Manchu Embroidery in Modern Clothing Design - Yingjian Xu (Art and Society, 2024)
“New Chinese Style” is a popular topic in modern clothing design in recent years. As a source of “New Chinese Style” design, Manchu embroidery features natural, simple, and sincere visual effects. It possesses high aesthetic value in aspects such as composition, modeling, and color matching. Combining modern clothing design with embroidery is beneficial for promoting Manchu culture and showcasing the essence of modern design. Incorporating Manchu clothing elements into modern clothing design can better emphasize the characteristics of the clothing itself. Therefore, this article takes Manchu embroidery patterns as the basis, provides a detailed analysis of the overview and innovation of Manchu embroidery culture, and on this basis, analyzes specific cases.